A Survey of Rice Sheath Blight Incidence in Key Rice-Growing Regions of Telangana and Tamil Nadu, South India - , N. Shiva Jyothi; , S. Sundaramoorthy (Archives of Current Research International, 2025)
Rhizoctonia solani, caused by many Rhizoctonia species, is a debilitating disease of rice (Oryza sativa) that causes significant yield losses in important producing locations. This study aims to determine the incidence of rice sheath blight in Tamil Nadu and Telangana in 2024. A comprehensive survey of rice-growing regions, involving nine districts in Telangana and three districts in Tamil Nadu, indicated varying illness incidences. Polasa (Telangana) has the highest percent disease incidence (PDI) of 74.23%, followed by Thidalveli (Tamil Nadu) with 71.26%. The tissue segment method used in pathogen isolation and identification identified Rhizoctonia spp. as the main agent. Morphological analysis indicated considerable differences between isolates in colony morphology, Sclerotial features, and growth patterns, indicating a diverse Rhizoctonia population throughout the examined sites.